Experimental and numerical investigation of biogas distributed combustion with different oxidizers in a swirl stabilized combustor - Ilbas, Mustafa; Guler, Nurhan Uregen; Sahin, Murat (ELSEVIER SCI LTD, 2021)
This study concentrates on combustion characteristics of biogas under differing oxidizers in a swirl combustor. The main purpose of this study is to investigate the combustion characteristics of biogas distributed combustion. In this study, the combustion process has been conducted with biogas and gas mixture of O2 - CO2 as oxidizer. Numerical investigations have been performed for three different oxidizers depending on O2 contents. Air, 100% O2 and gas mixture of O2 - CO2 which contains 40% O2 have been used as oxidizers in numerical investigations. The temperature distributions have been investigated both of experimentally and numerically with 40% O2 content. Emission behaviours have been performed numerically using a CFD code in which PDF/Mixture Fraction combustion and k-sigma standard turbulence models were used. Similar decreasing and increasing trends have been observed when experimental measurements and numerical predictions of temperature distributions are compared. The effect of oxidizer on emissions has been predicted. It is also concluded that combustion using 100% O2 has higher temperature values at close to the fuel inlet region as the combustion starts faster and more efficiently.
Keywords: Biogas; Distributed; Oxy-fuel; Combustion; Emission; EMISSIONS; Energy & Fuels; Engineering